Dolomitization of Ordovician Kelimoli carbonates linking to shale oil formation, western Ordos Basin: new insights from magnesium and strontium isotopes - Jing, Xianghui; Tian, Jingchun; Zhang, Lei; Li, Fengjie; Li, Han (Frontiers in Earth Science, 2025)
Deciphering the dolomitization process has great significance for high-quality hydrocarbon reservoir prediction in carbonate successions. The Ordovician Wulalike Formation provides shale oil in the western Ordos Basin, while lateral-contact marine dolostones of Kelimoli Formation contribute major reservoirs for extra hydrocarbons. Nonetheless, the origin and occurrence of dolostones are underexplored. Coupled with petrographic and lithologic analyses, this study attempts to investigate the dolomitizing fluid pathways and dolomitization pattern of Ordovician Kelimoli carbonates based on elemental and isotopic geochemistry. Extremely low Rb concentrations (i.e., less than 0.1) and Mn/Sr ratios (i.e., less than 2) of carbonates with micropores indicated that they are a valid proxy for geochemical signatures of coeval seawater. By contrast, dolostones developing vuggy pores showed a pronouncedly higher 87Sr/86Sr composition and Mn contents than other dolostone types, revealing that vuggy dolostones experienced meteoric water leaching and underwent geochemical alterations. Quantitative calculation of 87Sr/86Sr ratios and fluid-inclusion microthermometry revealed that the Kelimoli dolostones (i.e., dolograinstones and crystallized dolostones) were formed before meteoric water leaching influences at a deep-burial environment under seawater derivatives and sealed brine water. In evaporite–dolograinstone successions, increase in the magnesium isotopic composition (δ26Mg) with increasing burial depths indicated that the dolomitizing fluid migrated downwardly. Comprehensive isotopic evidences of 87Sr/86Sr, δ18O, and δ13C suggested that the dolomitizing fluid was a derivative of coeval seawater. In crystallized dolostone successions, upwardly heaving of δ26Mg ratios revealed that the dolomitizing fluid moved upwardly. The 87Sr/86Sr, δ18O, and δ13C and microthermometric evidence indicated that these dolostones were formed at a deep-burial, high-temperature environment and the dolomitizing fluid was derived from sealed brine water. Based on the above investigation, a comprehensive dolomitizing pattern was proposed for the studied section of Ordovician Kelimoli Formation.